PRIVATISASI BUMN SEBAGAI PILAR PEREKONOMIAN NASIONAL DALAM PERSPEKTIF HUKUM BISNIS - Raden Djuniarsono; Martin Roestamy; Endeh Suhartini (JURNAL ILMIAH LIVING LAW, 2023)
Guided by Pancasila and the 1945 Constitution, Indonesia should implement a welfare state with strategic planning for the welfare of the people through state ownership of certain business units that provide the greatest benefit for the welfare of the people by establishing companies that are majority or partially owned by the state, namely BUMN based on Good Corporate Governance (GCG). However, the role of BUMN has not been optimal and has not fulfilled the expectations of Article 33 of the 1945 Constitution and it is necessary to make improvements and arrangements, one of which is through privatization to improve and improve company performance. This research uses the juridical normative approach, namely, the law is conceptualized as norms, rules, principles, or dogmas, with data collection techniques used through library research methods and interviews and using qualitative analysis. Based on the results of the research conducted, there are many obstacles and problems in the application of the privatization method in reforming and structuring BUMN, especially related to separated state assets and the criteria for BUMN that can be privatized. For this reason, serious, systematic, tiered, and strategic efforts are needed in reforming and structuring state-owned companies, especially efforts to improve the performance and value of the company and are carried out by taking into account the legal side of the business and the state constitution. Keywords : Constitution; Privatization; GCG; Community Welfare